Teacher Strategies in Stimulating Early Reading Skills in 5–6-Year-Old Children at Asisi Kindergarten, Samarinda - Fahira Amanda Putri; Fitri Anjarwati (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
This study aims to describe teachers' strategies in stimulating early reading skills in children aged 5–6 years at Asisi Kindergarten Samarinda. Early reading is an important stage in literacy mastery that needs to be developed from an early age. The research subjects consisted of a B-class teacher and 15 children aged 5–6 years. Data collection was conducted through observation, interviews, and documentation, while data analysis used the Miles and Huberman interactive model, which includes data collection, reduction, presentation, and drawing conclusions. The results of the study indicate that teachers' strategies in stimulating early reading include three main aspects: (1) early identification of reading difficulties, (2) implementation of a multisensory approach based on the phonics method, and (3) teacher–parent collaboration through shared reading activities. The multisensory phonics approach combines visual, auditory, kinesthetic, and tactile aspects through letter cards, picture books, memory games, and alphabet songs. The results show an improvement in children's ability to recognize letters and sounds, as well as an increase in interest and motivation to read. Thus, a teacher's creative, adaptive, and collaborative strategies play an important role in developing early literacy in young children. Keywords: teacher strategy, early reading, early childhood